Perbandingan Pengencer Andromed dan CEP-2 terhadap Kualitas Spermatozoa Sapi Hasil Seksing dengan Sentrifugasi Gradien Densitas Percoll (COMPARISON OF ANDROMED AND CEP-2 DILUTER ON THE QUALITY OF LIMOUSIN CATTLE SPERMATOZOA FOLLOWING SEXING WITH PERCOLL G - ., Juniandri; Susilawati, Trinil; Isnaini, Nurul (Jurnal Veteriner; Vol 15 No 2 (2014), 2014)
The use of appropriate diluent is intended to ensure the physical and chemical requirements ofspermatozoa so that the quality, particularly capacitation can be maintained. This study aimed todetermine the quality of Limousin cattle sperm after sexing with density percoll centrifugation methodusing Andromed diluent and Cauda epididymal Plasma 2 (CEP-2) plus 10% egg yolk. Observations ofspermatozoa quality including : motility, viability, percentage of abnormal, concentrations, membraneintegrity and state of capacitation. The semen used were obtained from Limousin cattle at the Center forArtificial Insemination(BBIB) Singosari Malang, with motility criteria e” 70%. Data were analysed usinga paired T-test in order to determine differences in the use of thinning treatments at each layer. Theresults showed that both diluent, andromed and CEP-2 diluent plus 10% egg yolk were able to maintainthe quality of spermatozoa either in the upper and lower layers
Keywords: andromed, CEP-2 plus 10% egg yolks, spermatozoa, sexing, centrifugation gradient density percoll